Strengthening the MSME Through Institutional Cooperation Improvement Between MSME and Sharia Microfinance Institutions (SMFI) - Darsono Darsono; Darwanto Darwanto (Jurnal Ilmiah Al-Syir'ah, 2019)
Micro, Small and Medium Enterprise (MSME) is one of the pillars of the national economy because of the magnitude of the contribution made by MSME. It is even mentioned that MSME is an integral part of the country's economy. MSME in Indonesia is able to absorb the labor up to 97.02%. The contribution of MSME to GDP (57.08%) and investment (53.24%) also has a larger value when compared to large businesses. But in general, MSME has limited access to financial institutions. By these problems, the government has provided special financing of MSME through Microfinance Institutions (MFI). But in its implementation, externally MFI has obstacles of institutional aspects that have an impact on the variety of the MFI forms. While SMFI has Islamic financing methods that give priority to moral, ethical, and fair so efficiently it can encourage the participation of MSME entrepreneurs to succeed. This study formulates schemes or strengthening models of MSME to increase institutional cooperation between MSME and SMFI. The institutional strengthening scheme offered is expected to increase the contribution of MSME to the national economy.